The drug policy voices survey, 2018-2021 - Askew, Rebecca (UK Data Service, 2023)
The Drug Policy Voices project was funded by the ESRC between 2018 and 2021. The aim of the project was to engage people who use drugs (PWUD) into debates about drug policy reform. This was the first UK project designed to understand experiences and opinions, as well as improve knowledge about drug policy issues. A survey was conducted in 2020 to collect data on alcohol and other drug use, supply and sourcing, experience of criminal justice sanctioning, engagement in alcohol and other (AOD) drug treatment and drug user identity. 37 attitudinal questions were created using a blended values approach informed by Moral Foundations Theory (Graham et al., 2011, 2013; Haidt & Graham, 2007; Haidt & Joseph, 2004) and the four political positions that underpin drug policy (MacCoun & Reuter, 2001), in order to better understand opinions about key drug policy issues. Drug policy reform is high on the global political agenda. Since the turn of the 21st century, several countries have shifted from prohibition policy. Academics, policy-makers, practitioners, and non-government organisations (NGOs) are discussing (and advocating for) drug policy reform in the UK focussing on the usefulness and relevance of the Misuse of Drugs (MDA) Act 1971 and the Psychoactive Substances Act (PSA) 2016. Yet the voices of people who use drugs (PWUD) are largely absent from such debate and there is now increasing acknowledgement that contribution from those with lived experience is required to improve both the policy legitimacy and outcomes (UKDPC, 2012; Lancaster et al., 2014; Lancaster et al, 2015). This research used a mixed methods research design to engage PWUD into debates about drug policy, firstly, a survey to understand the values, attitudes and beliefs connected to drugs and drug policy, secondly, interviews to better understand the impact of policy on people with lived experience, and thirdly, workshops that debated key contentious drug policy issues. The project focused on the components of drug policy that are important to PWUD, through the inclusion and analysis of lived experience, we can better connect policy to those that it affects.